Analysis Model of Gateway in Wireless Mesh Network Based on M/M/1 Queuing Model - Taoshen Li; Hongyu Zhang; Jin Ye; Zhihui Ge (Dianxin kexue)
According to the characteristics of M/M/1 model and production features of customer request service in the wireless mesh network, a gateway queuing model in wireless mesh network based on M/M/1 model was constructed. The model puts the original disorder state sets in request service into order sets and it was queued at the gateway node. As a single service platform, gateway services in the whole collection. Then, to solve the model by using the mathematical method, the network system key parameters and target analysis function were derived. Finally, through verification experiment, the proposed model can obtain better network parameters in the network of non-saturated resource allocation. The theory analysis and experimental results show that the proposed model is reasonable and effective.